Criminal Liability for Debt Collector Online Loans Who Threaten Customers - Silviantinur Halimy; Yessy Dinasari; Danis Khalisa; Kristian Kristian (Syiar Hukum, 2022)
The ease of a series of processes offered online that lead to criminal acts by debt collectors with threats to customers. The purpose of the study is to determine the criminal liability of debt collectors online who collect with threats. The research method is normative juridical and the nature of the research is descriptive analysis. The results of the study are that debt collectors who commit criminal acts of threatening customers can be charged with the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. That criminal liability imposed on debt collectors who threaten customers can have a deterrent effect.